2022
DOI: 10.1080/19932820.2022.2059896
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of pancreatic β-cells dysfunction after vitamin D and calcium supplementation: a pilot study in a population of obese and prepubescent North-African children

Abstract: The mechanisms of diabetogenesis in children remain largely obscure. This study aimed to determine the impact of vitamin D and calcium supplementation on pancreatic β-cells function in terms of insulin secretion and sensitivity. This was a quasi-experimental study involving 30 obese and prepubescent Tunisian children (57% boys). During three months, the children received calcium and vitamin D supplementation at therapeutic doses. An oral glucose tolerance test (OGTT) was performed at the beginning and at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Several studies demonstrated that lower Vitamin D levels were associated with an increased risk of diabetes (Alam et al, 2016). A short-term supplementation with Vitamin D significantly improved function of beta cells; HbA1c levels were decreased (Alam et al, 2016;Devaraj et al, 2011;Gaddas et al, 2022;Joergensen et al, 2011;Satirapoj & Adler, 2014;Tonneijck et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that lower Vitamin D levels were associated with an increased risk of diabetes (Alam et al, 2016). A short-term supplementation with Vitamin D significantly improved function of beta cells; HbA1c levels were decreased (Alam et al, 2016;Devaraj et al, 2011;Gaddas et al, 2022;Joergensen et al, 2011;Satirapoj & Adler, 2014;Tonneijck et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As an index of pancreatic beta-cell function, we measured HOMA-β% as (20 fasting plasma insulin in μU/ml)/(FPG in mmol/l – 3.5) [ 20 ]. Hyperinsulinism was defined as the sum of insulin levels at 0th, 30th, 60th, 90th, and 120th min during OGTT > 300 microU/ml [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a glycemic level higher than 155 mg/dl at + 60′ after glucose load has been defined as a risk factor for T2DM in obese adolescents [ 22 ]. Moreover, total insulin obtained by sum during all the times of the test is useful to define insulin resistance [ 23 ].…”
Section: Introductionmentioning
confidence: 99%